REPRODUCTIVE HEALTH KNOWLEDGE AMONG ADOLESCENTS WITH INTELLECTUAL DISABILITIES: EDUCATIONAL AND INTERVENTION CHALLENGES - Arum Lusiana; Bambang Budi Raharjo; Widya Hary Cahyati; Evi Widowati; Dina Nur Anggraini Ningrum (Universitas Airlangga, 2026)
Introduction: Health education for intellectually disabled individuals can be provided, particularly about reproduction and sexuality. While their IQ grows more slowly, their reproductive organs reach maturity at a normal pace. This health education is very important to prevent unwanted pregnancies, sexually transmitted diseases (including HIV/AIDS), and cervical cancer. According to women National Community 2022, in the 10-year recording of Violence Against Women cases—from 2012 to 2021—2021 was recorded as the highest number of cases of Gender-Based Violence, where the data rose by 50% to 338,496 cases compared with 2020 as many as 215,694 cases. The National Commission on Violence Against Women has also documented cases of sexual violence against women with disabilities every year since 2017. Aim: The research was conducted to find out the understanding of reproductive health in intellectually disabled adolescents in the Temanggung Regency. Method: Data were collected from 10 informants who were selected using a qualitative case study design and purposive sampling. Result: It was established that out of the 6 main informants who were interviewed, 4 did not have any understanding about RH, while the remaining 2 had some knowledge to a minimum level. Despite the fact that adolescents have contributed positively toward attitude about reproductive health, they show very poor understanding about its implications. Conclusion: Knowledge was influenced by factors such as media exposure, while communication and motivation on reproductive health among adolescents were channeled by the roles of health workers, family, and peers.